Analysis of the response to two pharmacological protocols in patients with oral lichen planus: A randomized clinical trial. (29th July 2021) - Polizzi, Alessandro; Santonocito, Simona; Lo Giudice, Antonino; Alibrandi, Angela; De Pasquale, Rocco; Isola, Gaetano
Abstract: Objective: To evaluate the effectiveness of two different therapies on oral lichen planus (OLP) treatment through the analysis of OLP symptoms and signs and to analyze the risk of side effects related to the adopted protocols. Methods: Thirty‐eight patients with OLP were selected according to van der Meij and van der Waal clinical and histopathological criteria. Through a randomized design, 19 patients received Tacrolimus 0.1% ointment (T group) and 19 an anti‐inflammatory mouthwash (M group) composed of calcium hydroxide 10%, hyaluronic acid 0.3%, umbelliferone, and oligomeric proanthocyanidins. The patients were examined on a regular basis for OLP symptoms, signs, and disease severity score changes over a 3‐month follow‐up period. Results: Both treatments were effective in the reduction of OLP signs and symptoms. However, at 3 months (T3), in comparison with the M group, T group patients showed significantly lower mean values of OLP signs ( p  = 0.035), symptoms ( p  = 0.045), and disease severity scores ( p  = 0.041). Moreover, the Spearman test showed that there was a significant correlation between OLP signs and symptoms at each follow‐up session in all patients. Conclusions: Both treatments demonstrated a significant approach to control OLP. However, tacrolimus determined a more effective improvement in OLP signs and symptoms compared to anti‐inflammatory mouthwash at 3‐month follow‐up.